A home for the marine - King, Kellie A. (King, Kellie A.. Ballad Inn romance., 2024)
Retired marine Gideon Holder knows he and his baby girl need a fresh start. The job at the charming sister-owned Ballad Inn is beyond his expectations—as is widowed nurse Margo Ballad. They both know what it is to lose someone…and how it feels to still hope for love. But finding that spark is one thing. Finding the courage to take the leap is quite another.